2015
DOI: 10.1080/2162402x.2015.1055993
|View full text |Cite|
|
Sign up to set email alerts
|

Increased sMICA and TGFβ 1 levels in HNSCC patients impair NKG2D-dependent functionality of activated NK cells

Abstract: Abbreviations: ADCC, antigen-dependent cellular cytotoxicity; HNSCC, head-and-neck squamous cell carcinoma; HSCT, haploidentical stem cell transplantation; KIR, killer cell immunoglobulin-like receptor; NCR, natural cytotoxicity receptor; NK, natural killer; NKG2D, natural-killer group 2, member D; vitsMICA/NKG2DL, soluble major histocompatibility complex Class I chain-related peptide A; TGFb1, transforming growth factor beta 1; TIEM, tumor immune escape mechanismDisseminated head-and-neck squamous cell carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 47 publications
(73 reference statements)
6
40
1
2
Order By: Relevance
“…Previously, we could show a correlation of high sMICA plasma levels and impaired NK cell cytotoxicity in patients with HNSCC (33, 41). Since these studies only investigated sMICA in NKG2D-dependent tumor immune escape, in the current study, we determined the levels of all the shed NKG2DLs (sMICA, sMICB, and sULBP1–3) in plasma samples of 44 HNSCC patients (patients’ characteristics are summarized in Table 1).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Previously, we could show a correlation of high sMICA plasma levels and impaired NK cell cytotoxicity in patients with HNSCC (33, 41). Since these studies only investigated sMICA in NKG2D-dependent tumor immune escape, in the current study, we determined the levels of all the shed NKG2DLs (sMICA, sMICB, and sULBP1–3) in plasma samples of 44 HNSCC patients (patients’ characteristics are summarized in Table 1).…”
Section: Resultsmentioning
confidence: 79%
“…However, shedding of NKG2DLs leads to impaired cytotoxicity of NK cells and T cells due to loss of antigenic NKG2DLs and shed NKG2DL (sNKG2DL)-induced downregulation of NKG2D (2426). Consequently, patients suffering from various cancers (2733) demonstrated an inverse correlation of sMICA plasma levels and NKG2D-dependent NK cell cytotoxicity. Since all sNKG2DLs engage with a common receptor, the cumulative level of all sNKG2DLs is decisive for their biological/clinical effect.…”
Section: Introductionmentioning
confidence: 99%
“…However, they reported an increase in cellular apoptosis that was restricted to the circulating CD56 dim population (22). The reduced percentage of circulating CD56 bright cells was confirmed in head and neck cancer patients by two additional distinct studies (23,24). In contrast, Mamessier et al (25) observed that the amount of circulating CD56 bright NK cells in BC patients increased in relation to the grade of malignancy.…”
Section: Cd56mentioning
confidence: 87%
“…Marked levels of the soluble form of the MHC class I-related chain A, identified as a human NKG2D ligand, were found in the sera of patients with disseminated head-and-neck squamous cell [26] and human hepatocellular carcinomas [27] and neuroblastoma [28]. This tumor-derived soluble inhibitory ligand appears to be responsible for the downregulation of NKG2D expression in NK cells and subsequent impaired NKG2D-mediated cytotoxicity in patients with advanced disease.…”
Section: Discussionmentioning
confidence: 98%